Current management of hypertension in hospital. Issue 6074 (4th June 1977) - Heller, R F; Rose, G
Abstract : A study of the notes of 1784 patients new to two London hospitals found a blood-pressure recording in 1027 (58%). Only 423 (32%) of all outpatients had had a blood-pressure recording on their first visit. Of 144 patients with hypertension (systolic greater than or equal to 160 mm Hg or diastolic greater than or equal 100 mm Hg or both) a check recording was made in 89 (62%) and 18 (12%) were put on treatment. We conclude that the opportunity that a hospital visit provides for blood-pressure screening is being incompletely used, and that the discovery of hypertension often does not lead to further action.